Pengembangan Buku Tamu Berbasis Website Sekretariat DPRD Kabupaten Magetan - Arwanda Setyo Budi (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
Regional House of Representatives (DPRD) of Magetan Regency to enhance the efficiency and effectiveness of visit data management. The system was developed using the Rapid Application Development (RAD) method, utilizing the Laravel framework and MySQL database. The implementation of this system is expected to replace the time-consuming and inefficient manual processes, such as guest book entry and data retrieval. The web-based system allows guests to digitally input their institutional origin, purpose, and objectives of their visit, which are then managed by the administrator for reporting and data analysis.The system development process began with needs analysis, design using UML diagrams, and implementation through web-based technology. System testing was conducted using the Black Box Testing method to ensure all system functions operate as specified. The research findings demonstrate that the system effectively reduces data processing time, increases accuracy, and facilitates the management of visit information. Thus, this information system not only provides practical solutions for DPRD Magetan but also serves as a model for similar developments in other institutions. This study offers significant theoretical and practical contributions to the advancement of information technology in the governmental sector